Comoros : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1995)
This paper reports economic developments in Comoros during the 1990s. Growth picked up during 1991-93, but there was continuing pressure on public finances and the balance of payments. After widening sharply in 1991, the primary budget balance improved significantly during the second half of 1992 and in 1993, as strong measures were taken to reduce current expenditures. The current account continued to be weak, owing to the narrow export base and the declining export prices of vanilla and cloves.